Day to Day Life of Transnational Couples - Ferreira, Tatiana (2016)
In this chapter we focus on the ways that transnational spatial mobility affects the production and reproduction of daily life of couples when one of the partners migrates alone. The aim is to examine the impact of male migration on day to day life of couples in which the partners are geographically separated across nation-state borders. V/e will adopt a transnational approach in order to recognize the importance of the connections between migrants and their family members back home. Living apart together poses new challenges to partnerships in their everyday lives and requires a process of negotiation with the ones that stay behind (Levin and Trost 1999,2004;Pribilsky 2004; Grassi 2014,2015).